Heterozygous P32/C1QBP/HABP1 Polymorphism rs56014026 Reduces Mitochondrial Oxidative Phosphorylation and Is Expressed in Low-grade Colorectal Carcinomas - Raschdorf, Annika; Sünderhauf, Annika; Skibbe, Kerstin; Ghebrehiwet, Berhane; Peerschke, Ellinor I.; Sina, Christian; Derer, Stefanie (Frontiers in Oncology, 2021)
Rapid proliferation of cancer cells is enabled by favoring aerobic glycolysis over mitochondrial oxidative phosphorylation (OXPHOS). P32 (C1QBP/gC1qR) is essential for mitochondrial protein translation and thus indispensable for OXPHOS activity. It is ubiquitously expressed and directed to the mitochondrial matrix in almost all cell types with an excessive up-regulation of p32 expression reported for tumor tissues. We recently demonstrated high levels of non-mitochondrial p32 to be associated with high-grade colorectal carcinoma. Mutations in human p32 are likely to disrupt proper mitochondrial function giving rise to various diseases including cancer. Hence, we aimed to investigate the impact of the most common single nucleotide polymorphism (SNP) rs56014026 in the coding sequence of p32 on tumor cell metabolism. In silico homology modeling of the resulting p.Thr130Met mutated p32 revealed that the single amino acid substitution potentially induces a strong conformational change in the protein, mainly affecting the mitochondrial targeting sequence (MTS). In vitro experiments confirmed an impaired mitochondrial import of mutated p32-T130M, resulting in reduced OXPHOS activity and a shift towards a low metabolic phenotype. Overexpression of p32-T130M maintained terminal differentiation of a goblet cell-like colorectal cancer cell line compared to p32-wt without affecting cell proliferation. Sanger sequencing of tumor samples from 128 CRC patients identified the heterozygous SNP rs56014026 in two well-differentiated, low proliferating adenocarcinomas, supporting our in vitro data. Together, the SNP rs56014026 reduces metabolic activity and proliferation while promoting differentiation in tumor cells.